NAZORAT MATERIALLARI TAYORLASHNING METODIK ASOSLARI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In this article "Methodological analysis of monitoring and evaluation". Traditional means of control, information about the subject of research are given.
Keywords: quality, problem, education, program, modern control tools, traditional inspection.